The Law of succession concerning Moldavian women in the 14th-17th centuries: a comparative study - Zabolotnaia, Lilia (Balcanica Posnaniensia. Acta et studia, 2013)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The hereby article presents an analogous analysis of the patrimonial and inheritance legal status of Moldovan women, contrasted with their counterparts in the neighbouring countries, such as Lithuania, Romania, Transylvania, Russia, Serbia and Montenegro. In author’s opinion, woman’s patrimony served as a warranty for her legal and social status. Officially, women could not participate in the political life of the state, yet, some of them, possessing large estates, were indeed influential. Empowered by the autonomous possession and management of their assets, women attained some economic independence in the social sphere. Characterizing the differences and similarities in the status of women regarding the laws of succession, it should be observed that too much emphasis was placed on the legal inequality of women in different countries. In consequence, a stereotype was established in historical literature. Frequently, in European countries, an inconsistency or even a contradiction between legislation and law enforcement could be observed.